Autism Spectrum Disorders: Is Mesenchymal Stem Cell Personalized Therapy the Future?. (13th February 2012) - Siniscalco, Dario; Sapone, Anna; Cirillo, Alessandra; Giordano, Catia; Maione, Sabatino; Antonucci, Nicola
Abstract : Autism and autism spectrum disorders (ASDs) are heterogeneous neurodevelopmental disorders. They are enigmatic conditions that have their origins in the interaction of genes and environmental factors. ASDs are characterized by dysfunctions in social interaction and communication skills, in addition to repetitive and stereotypic verbal and nonverbal behaviours. Immune dysfunction has been confirmed with autistic children. There are no defined mechanisms of pathogenesis or curative therapy presently available. Indeed, ASDs are still untreatable. Available treatments for autism can be divided into behavioural, nutritional, and medical approaches, although no defined standard approach exists. Nowadays, stem cell therapy represents the great promise for the future of molecular medicine. Among the stem cell population, mesenchymal stem cells (MSCs) show probably best potential good results in medical research. Due to the particular immune and neural dysregulation observed in ASDs, mesenchymal stem cell transplantation could offer a unique tool to provide better resolution for this disease.